DESCRIPTION OF SLEEP QUALITY IN PATIENTS WITH CHRONIC RENAL FAILURE IN THE INPATIENT ROOM OF BAPTIST HOSPITAL KEDIRI - Dyah Ayu Kartika Wulan Sari; Vitaria Wahyu Astuti; Rifka Dwi Ayu Desitasari (Suluh Adiluhung Publisher (SAPub), 2025)
Disturbed and poor sleep quality in patients with chronic renal failure can have a negative impact on physical, mental and can lead to patient appearance as well as cognitive and memory dysfunction, irritability, decreased alertness and concentration. This study used a descriptive design with purposive sampling technique. The sample in this study totalled 15 respondents. This research instrument is The Pittsburgh Sleep Quality Index (PSQI) which consists of 19 questions. The results of this study most of the sleep quality of chronic renal failure patients treated in the Inpatient Room of Baptist Hospital Kediri had poor sleep quality as many as 9 respondents (60%). Based on aspects of subjective sleep quality obtained as many as 14 respondents (93.3%) revealed quite poor sleep quality, aspects of sleep duration in chronic renal failure respondents mostly had a sleep duration 6-7 hours as many as 8 respondents (53.3%), aspects of sleep lethality in chronic renal failure patients most patients had very good sleep lethality or scored 0 as many as 14 respondents (93.3%). This study uses frequency distribution analysis for respondent characteristics and sleep quality analysis. Research on the description of the quality of sleep of chronic renal failure patients in the Inpatient Room of the Baptist Hospital Kediri most of the patients‘ sleep quality is poor, this can be seen from various aspects of sleep quality that appear, in the aspect of subjective sleep quality most of the patients’ sleep quality is quite poor, and most respondents experience sleep disorders and daytime sleep dysfunction.